Current condition of the ornithofauna of the Alexandria Dendrological Park - Prychepa, M. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
The species composition of birds of the Alexandria Dendrological Park has been analyzed. The studies were conducted in 2008–2018. In total 148 bird species were registered (35% of the ornithofauna of Ukraine). Birds were analyzed by biotopic groups, nature of stay and type of nesting. It was found that in the conditions of the Alexandria Dendrological Park, the dominant ecological groups were dendrophiles (80 species). According to the nature of their stay, nesting birds accounted for 90 species, migratory – 48 species, wintering – 31 species. Depending on the type of nesting, canopy-nesting and hole-nesting birds prevailed – 27.8 and 24.4% respectively. Representatives of Piciformes and Passeriformes make up a significant part of the nesting species, which is 10 and 57.8% respectively. Falconiformes are represented by 4 species, which is 4.4% of the total number of nesting species. The value of the park also consists in the presence of favorable wetlands for wintering and forage migration of a number of taxon birds in its territory. As a result, the bird population is growing. The emergence of new bird species in recent years can provide a unique indication of the importance of ornithocenosis in these areas. This concerns in particular Green Woodpecker, Black kite, Honey Buzzard, Night Heron, Stock Dove, Spotted Crake. It has been established that new species appear in the park, settling from nearby or remote areas. During the years of observation, 9 species from the Red Data Book of Ukraine (Ciconia nigra, Netta rufina, Haliaeetus albicilla, Milvus migrans, Buteo rufinus, Pandion haliaetus, Bucephala clangula, Picus viridis, Columba oenas) have been recorded. The factors influencing the species composition of birds have been analyzed. They include felling of trees, thinning of shrubs, uncontrolled recreation and direct predation from dogs. One of the main problems limiting the number of birds in the park is trespassing of logging processes, in particular during the nesting period. In the future, more comprehensive studies are planned on the quantitative composition of birds, as well as features of the topical distribution according to the biocenosis.